Controlled synthesis of phosphorus-based nanostructures for lithium ion battery application - Yang, Dan (2016)
For this project, metal-rich cobalt phosphides (e.g., orthorhombic Co2P) are first explored as potential anode materials because of good thermal stability, relatively low charge-discharge potential, as well as metallic property. The as-resulted products, especially carbon-coated Co2P nanorods, have achieved excellent stability during cycling. As a continuation and improvement of the previous work, we synthesized pure CoP by holding the reaction at high temperature for enough long time, to guarantee the fully release of phosphorus in the precursor.The above process not only leads to pure-phase CoP, but also results in some interesting carbon-coated hollow nanostructures, which benefits storage and transportation of Li+ and results in remarkable stability and rate performance (e.g., a discharge capacity of 630 mA h g−1 was achieved at 0.2 C at 100th cycle, and at a high rate of 5 C, the reversible capacity was 256 mA h g-1.).On the other hand, to satisfy the future high-power application, ultrathin 2D structure of amorphous phosphates (FePO4, Co3 (PO4)2), Mn3 (PO4)2) were synthesized. In particular, 2D FePO4 with ordered porous structure is tested as cathode for LIB and a high capacity of 160 mAh g-1 (for the first cycle) and good charge/discharge stability can be achieved for such unique structure.